2016
DOI: 10.1080/23311975.2016.1194174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychological capital on organizational citizenship behavior: Moderating role of emotional intelligence

Abstract: The role of emotional intelligence (EI) towards nurturing citizenship behavior is still imperfectly certified and is awaited for investigation. At the same time, the growing interest in recent years on psychological capital (self-efficacy, hope, resilience, and optimism) within the managerial literature is sparsely researched in Indian context. Therefore, the purpose of the study is set to investigate (a) the relationship of psychological capital (Psycap) on organizational citizenship behavior (OCB) and (b) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 56 publications
10
73
0
1
Order By: Relevance
“…Although some studies have proven the effect of EI on job performance and job burnout, the related research on how EI affects job performance and job burnout has not been fully certified and is still waiting for investigation. Pradhan confirmed the hypothesis that "EI plays a regulatory role between psychological capital and organizational citizenship behavior" (Pradhan et al, 2016). Moreover, EI and psychological capital can predict job performance and job burnout.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although some studies have proven the effect of EI on job performance and job burnout, the related research on how EI affects job performance and job burnout has not been fully certified and is still waiting for investigation. Pradhan confirmed the hypothesis that "EI plays a regulatory role between psychological capital and organizational citizenship behavior" (Pradhan et al, 2016). Moreover, EI and psychological capital can predict job performance and job burnout.…”
Section: Introductionmentioning
confidence: 59%
“…EI can allow individuals to effectively regulate their emotions and promote the formation of self-efficacy. In addition, some scholars have shown that positive psychological orientation can help individuals develop better EI to maintain healthy interpersonal relationships and achieve the best organizational performance (Pradhan et al, 2016). In a recent study, it was also shown that the EI of managers plays an important role in obtaining psychological capital (Sarwar et al, 2017).…”
Section: H4mentioning
confidence: 99%
“…As shown by Pradhan, Jena, Bhattacharya, & Nisar (2016), EQ is correlated with positive-sum behaviours, such as organisational citizenship (Morrison, 1994). Consistent with a claim that positive-sum collaboration helps in life success, a meta-analysis of research where EQ is taught in school has shown improvements up to 18 years post-intervention, such as improvements in high school graduation rate, and lower sexual risktaking (Taylor, Oberle, Durlak, & Weissberg, 2017).…”
Section: Emotional Intelligencementioning
confidence: 51%
“…The link between EI and sustainable well-being for individuals and environments has recently attracted attention in the psychological literature. Several studies have revealed the main role of EI in the promotion of pro-social and pro-environmental behaviours, relatedness, well-being and sustainability (Callea et al, 2019;Ojala, 2013;Petrides et al, 2016) and trait EI was found to be directly relevant to job satisfaction, job adaptability, entrepreneurial behaviour, and engagement at work (Ahmetoglu, Leutner, & Chamorro-Premuzic, 2011;Akhtar et al, 2015;Pradhan, Jena, & Bhattacharya, 2016). For instance, in two studies exploring the personality traits and EI of 416 university students, Di Fabio and Saklofske (2019) employed four commonly used personality questionnaires, as well as The Intrapreneurial Self-Capital Scale (ISCS) and the Trait Emotional Intelligence Questionnaire Short Form (TEIQue-SF), to demonstrate that trait EI explained individual intrapreneurial characteristics that are vital for the sustainable construction of one's career and life paths.…”
Section: Emotional Intelligence and Sustainabilitymentioning
confidence: 99%